Flexitarian Diet and Weight Control: Healthy or Risky Eating Behavior? - Forestell, Catherine A. (Frontiers in Nutrition, 2018)
A carefully planned vegetarian diet meets nutrition recommendations by providing essential nutrients and lowering levels of saturated fat and cholesterol. Because balanced diets that limit or exclude meat tend to be lower in calories than omnivorous diets, it has been suggested that vegetarian eating patterns may be motivated by weight control. This view has been supported by findings demonstrating that vegetarians have a higher rate of disordered and restrained eating than non-vegetarians. Other findings suggest that weight control is a primary reason identified by adolescents and young adults for eliminating items such as meat and other animal products from their diet. Thus, it has been suggested that vegetarianism may provide a socially acceptable means to control body weight. However, this may be an over-generalization. Vegetarians are a heterogeneous group of individuals with radically different eating habits. Moreover, they are often compared to omnivores who eat meat on a regular basis. These omnivorous eating habits do not represent a growing subset of the population, many of whom are adopting a flexitarian diet that involves only the occasional consumption of meat. The goal of the current paper will be to demonstrate that semi-vegetarians and flexitarians are categorically different from vegans, lacto-ovo-vegetarians, and omnivores and describe the motivations as well as the positive and negative health implications that are associated with dietary patterns that limit the intake of meat. It is important for us to understand the motivations and behaviors that are characteristic of flexitarians in order to develop effective evidence-based strategies to address unhealthy eating behaviors.